Development of deep learning models for high-resolution exposome mapping and health impact assessment - Luan, Lan; Daoyu, Zhu (Frontiers in Public Health, 2025)
IntroductionThe study of environmental health and the exposome is becoming increasingly vital as researchers aim to untangle the complex interactions between environmental exposures and human health outcomes. Traditional exposome mapping methods often face limitations, such as low spatial-temporal resolution, challenges in integrating multi-modal data sources, and inadequate handling of uncertainties in exposure quantification.MethodsTo address these gaps, we introduce an innovative framework that leverages advanced deep learning techniques, adaptive optimization strategies, and multi-scale data integration to achieve high-resolution exposome modeling. Central to our approach is the Adaptive Multi-Scale Exposure Network (AMSEN), a hierarchical deep learning model designed to harmonize diverse data streams, such as satellite imagery, wearable sensors, and geospatial analytics, while addressing the challenges of multi-scale variability and measurement uncertainties. AMSEN incorporates cross-modal fusion mechanisms, spatiotemporal feature extraction, and uncertainty quantification. Complementing AMSEN, the Adaptive Exposure Optimization Strategy (AEOS) enhances model efficiency and accuracy through dynamic resource allocation, uncertainty-guided refinement, and domain-specific prior enforcement.ResultsThese methodologies significantly advance the capabilities of exposome research by providing a robust, adaptive, and high-resolution modeling framework.DiscussionThe experimental findings highlight the effectiveness of our approach, showcasing enhancements in exposure prediction precision, computational performance, and practical insights for public health policymaking. This work aligns with the objectives of advancing environmental health sciences by offering novel tools for exposome quantification and health impact assessment.